(untitled) (Revista de Ciências Agroveterinárias, 2018)
Cats are among the most common pets in the world. The close relationship between human beings and cats supports the importance of epidemiologic studies on feline diseases. Therefore, this study showed the occurrence of infectious diseases in cats at the Veterinary Clinics Hospital (HCV) of Santa Catarina State University (UDESC), in Lages (SC, Brazil), as well as identifying the major clinical signs presented in each affection. Hence, 825 medical records were reviewed, from February 2013 to July 2015. Among the reviewed records, 20/285 (2,42%) were diagnosed with infectious diseases. The distribution of infectious diseases was: viral 12/20 (60,00%); bacterial 4/20 (20,00%); fungal 3/20 (15,00%) and caused by protozoa 1/20 (5,00%). Among these infectious diseases, the most diagnosed agent was Feline Leukemia Virus (FeLV) [12/20 (60,00%)]. The most observed clinical signs were anemia (6/12 [50,00%]), followed by leukemia (4/12 [33,33%]) and lymphoma (2/12 [16,67%]). The study also showed the occurrence of infectious diseases according to some selection standards, for instance, breed, age, sex, outdoor access, inhabiting with other pets and vaccination status. The most affected group of animals were non-vaccinated male cats, which had direct contact with other felines and outdoor access, demonstrating the close relationship between the lack of health care and the occurrence of feline infectious diseases.